2017
DOI: 10.17269/cjph.108.6091
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation and factors associated with colorectal cancer incidence in Manitoba

Abstract: OBJECTIVES: Although individuals living in areas with lower household income have been shown to have higher rates of mortality from colorectal cancer (CRC), findings on the effect of income on CRC incidence in countries with universal health care have been inconsistent. There are limited data from Canada. We investigated the geographic variation and factors associated with CRC incidence in Manitoba, a central Canadian province. METHODS:The Manitoba Cancer Registry and Manitoba Health population registry were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Descriptive summary of included studies concerning study location, setting and study design are shown in Figure 2 . All eligible studies were conducted spanning five countries that include Canada [ 41 ], United States [ 11 , 32 , 42 ], France [ 43 ], Portugal [ 35 ], and Iran [ 33 , 34 , 36 , 37 , 38 , 39 ]. Comparing study locations based on the WHO regions, four studies [ 11 , 32 , 41 , 42 ] accounted for the Region of the Americas (AMR), two studies [ 35 , 43 ] from the European Region (EUR) and six studies [ 33 , 34 , 36 , 37 , 38 , 39 ] were performed in the Eastern Mediterranean Region (EMR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive summary of included studies concerning study location, setting and study design are shown in Figure 2 . All eligible studies were conducted spanning five countries that include Canada [ 41 ], United States [ 11 , 32 , 42 ], France [ 43 ], Portugal [ 35 ], and Iran [ 33 , 34 , 36 , 37 , 38 , 39 ]. Comparing study locations based on the WHO regions, four studies [ 11 , 32 , 41 , 42 ] accounted for the Region of the Americas (AMR), two studies [ 35 , 43 ] from the European Region (EUR) and six studies [ 33 , 34 , 36 , 37 , 38 , 39 ] were performed in the Eastern Mediterranean Region (EMR).…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed articles were published in the year 2016 to 2021. Seven of these quantitative studies resumed cross sectional study design [ 33 , 34 , 35 , 39 , 41 , 42 , 43 ], two studies were conducted using retrospective cohort [ 11 , 32 ], and three articles of ecological studies [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cancer rates may be confounded by distributions of unknown or unmeasured factors related to cancer (85). Ecologic fallacy 24 Results should be interpreted only in the context of area of residence (42).…”
Section: Limitation Counts a Example 1 Examplementioning
confidence: 99%
“…Only a single year of data was used for covariates, which may not be reflective of early (or latter) time periods (42,72). Self-reported measurements, recall bias and other information biases (excluding misclassification of exposure)…”
Section: Lack Of Information At the Individual-level On Sociodemographics And Health Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation